Performance Accountability Financial Reports of Saving and Loan Cooperatives in East Lombok (Study on KSUSPPS Bina Al-Mandiri Syaria'ah) - Salmato; Baiq Anggun Hilendri Lestari; Lalu Takdir Jumaidi (International Journal of Business and Applied Economics, 2023)
This study analyzes the accountability of financial reporting performance in one of the cooperatives in East Lombok Regency, the KSUSPPS Bina Al-Mandiri Syari'ah Cooperative. This study aims to determine the extent to which the performance accountability of the KSUSPPS Bina Al-Mandiri Syari'ah Cooperative's financial reports is accountable to members and the public. This study uses a descriptive-qualitative approach, collecting data through observation, interviews, and documentation. The results showed that the KSUSPPS Bina Al-Mandiri Syari'ah Cooperative needed to be more fully accountable and transparent in managing the cooperative. KSUSPPS Bina Al-Mandiri Syari'ah Cooperative, in compiling financial reports, has included proof of transactions but has not integrated them; disclosures are made only in the form of financial report items, and financial reports are available for each unit containing a statement of financial position and profit and loss statement. Documents for cooperative activities are available in full and can be accessed by the community and members.